DESIGN AND IMPLEMENTATION OF AN EARTHQUAKE VICTIM SEARCH SYSTEM WITH VIDEO STREAMING AND PATH TRACKING BASED ON RASPBERRY PI 4 - Glenn Manurung, Nicholas
Earthquakes are one of the natural disasters that can cause significant damage to infrastructure and buildings, posing major challenges in the process of evacuating victims. Rescuing victims from building debris requires effective strategies and supporting technology to be carried out quickly and accurately. In this research, the authors developed an earthquake victim search system based on Raspberry Pi 4, equipped with video streaming and path tracking features. This system is designed to provide real-time visual information about the surrounding environment and the paths taken by the search device, which is then conveyed to the rescue teams outside the disaster area. With this information, rescue teams can more easily determine the location of victims and plan optimal evacuation routes. The system developed by the authors uses Raspberry Pi 4 as the control center and WiFi signal transmitter. With the ability to function as an independent access point, Raspberry Pi 4 can